Perbandingan Ekuitas Merek Produk Kosmetik Asing Orea Dengan Kosmetik Lokal - Maretta Edgina Damayanti; Berta Bekti Retnowati (JEMAP, 2019)
Brand equity became important for a product because it referred to a set of brand assets and liabilities related to a brand, its name and its symbol, which add or subtract the value provided by a good or service to the company or its customers. Departing from this understanding, this study aimed to conduct empirical differences or comparative studies on local cosmetic products represented by local brand the Wardah and South Korea cosmetic product represented by Etude House. The data required in this study was obtained through interviews using a questionnaire. Interviews were conducted to students at four Universities in Semarang, namely Soegijapranata Chatolic University, Dian Nuswantoro University, Diponegoro University, and Semarang State University. Data analysis for the purpose of this study was conducted using the Mann Whitney Comparative Test (U-test). The results showed that brand awareness, brand association, perceived quality of Wardah and Etude House cosmetics were significantly different, while the brand loyalty to Wardah and Etude House cosmetics brand was the same.